Pemanfaatan Lahan Pembuangan Sampah Menjadi Taman Toga - Alrahma, Lustia Anggun; Andesti, Kiya; Nabilah, Vina Haiffa; Stiawan, Muhammad Okhy; Syahrul, Muhammad Gilang; Afriani, Ririn; Putra, Dhanu Ario; Handayani, Tita Septi (Jurnal Karya Nyata Pengabdian, 2026)
Family medicinal plants (TOGA) provide numerous benefits to human life. Since ancient times, these efficacious plants have been used by people as herbal medicines. Therefore, the Community Service Program (KKN-T) was carried out to provide knowledge and understanding of the benefits of TOGA. This KKN-T activity was carried out in RT 05, Pematang Gubernur Village, Muarabangkahulu District, Bengkulu City Regency. In RT 05, there are still many vacant plots of land owned by residents. The activity began with requesting permission from government officials, the RT 05 Management, and residents to conduct outreach regarding TOGA and create a TOGA garden. Based on the outreach, it can be said that the residents of Bogak Besar Village were quite enthusiastic in listening to the outreach about utilizing vacant land for TOGA.